Nuclear receptors in oral cancer-Emerging players in tumorigenesis. (28th June 2022) - Gangwar, Shailendra Kumar; Kumar, Aviral; Jose, Sandra; Alqahtani, Mohammed S.; Abbas, Mohamed; Sethi, Gautam; Kunnumakkara, Ajaikumar B.
Abstract: Oral cancer has been a global concern for decades, with an estimated 377, 713 new cases and 177, 757 deaths worldwide, according to the GLOBOCAN 2020. Despite extensive research over the years, there is still a need to establish therapeutic targets to improve patient survival in oral tumorigenesis. Nuclear receptors (NRs) are transcription factors that regulate various biological processes such as growth, differentiation, development, and metabolism, and their aberrant expression has been reported in many diseases, including cancers. Deregulation of different NRs has been linked to various alterations such as mutations, epigenetic changes, and impaired signaling cascades by other proteins and molecules. Very few studies have shown the diagnostic and prognostic potential of NRs in oral cancer. These receptors have been targeted using a plethora of agonists and antagonists, leading to inhibition of tumor proliferation, migration and invasion, and inducing apoptosis, suggesting that NRs could serve as plausible targets for treating oral malignancies. In this review, we focus on the involvement of NRs in oral tumor pathogenesis and highlight the importance of targeting NRs using various agonists and antagonists that could serve as a potential strategy for the prevention and treatment of oral malignancies. Highlights: Aberrant regulation of nuclear receptors has been frequently encountered in oral cancer. Nuclear receptors have been closely linked with tumor progression and metastasis in oral cancer. Targeting nuclear receptors can serve as an important strategy for management of oral cancer.